(untitled) (Swiss Medical Weekly, 2012)
BACKGROUND: Impairment of the vasorelaxant responses have been reported in diabetes mellitus. In this study, the roles of the KATP channel and rho kinase pathway were evaluated by using the KATP channel opener cromakalim and Rho-kinase inhibitor HA 1077 in diabetic rat aorta. METHODS: Adult male Wistar rats weighing (250–300 g) were divided into diabetic and control groups. Diabetes was induced by a single intraperitoneal injection of streptozotocin (STZ, 55 mg/kg/i.p). RESULTS: Vasodilator responses induced by cromakalim (10–7 to 10–3M) and HA 1077 (10–6 to 10–4M) were significantly less in diabetic rings compared with control rings (p <0.01). The decrease in the relaxant effect of cromakalim was more in endothelium-denuded rings compared to the endothelium-intact rings (p<0.05). There were no significant differences between endothelium intact and non-intact rings in the presence of HA 1077. When two drugs were administered together, relaxation was significantly less than with seperate administration of each drug in the diabetic group (p <0.01). Pre-treatment with N omega-nitro-L-arginine methylester (L-NAME) (10–6 to 10–4M), an NO synthase inhibitor, significantly decreased the relaxant response to cromakalime and HA 1077 in both the control and diabetic groups (p <0.05). CONCLUSIONS: These results suggest that the impaired relaxant effects were further decreased depending on KATP channel activity but the effects of Rho-kinase enzyme inhibitors on relaxation responses were not significantly changed in diabetes mellitus.